Optimization of Nozzle Diameter and Printing Speed for Enhanced Tensile Performance of FFF 3D-Printed ABS and PLA - I. S. ELDeeb; Ehssan Esmael; Saad Ebied; Mohamed Ragab Diab; Mohammed Dekis; Mikhail A. Petrov; Abdelhameed A. Zayed; Mohamed Egiza (Journal of Manufacturing and Materials Processing)
Fused Filament Fabrication (FFF) is a widely adopted additive manufacturing technique, yet its mechanical performance is highly dependent on process parameters, particularly nozzle diameter and printing speed. This study evaluates the influence of these parameters on the tensile behavior of Acrylonitrile Butadiene Styrene (ABS) and Polylactic Acid (PLA), aiming to determine optimal conditions for enhanced strength. ASTM D638-Type IV specimens were printed using nozzle diameters ranging from 0.05 to 0.25 mm and speeds from 15 to 80 mm/s. For ABS, tensile strength increased from 56.46 MPa to 60.74 MPa, representing a 7.6% enhancement, as nozzle diameter increased, with the best performance observed at 0.25 mm and 45 mm/s, attributed to improved melt flow and interlayer fusion. PLA exhibited a non-linear response, reaching a maximum strength of 89.59 MPa under the same conditions, marking a 22.3% enhancement over the minimum value. The superior performance of PLA was linked to optimal thermal management that enhanced crystallinity and interlayer bonding. Fractographic analysis revealed reduced porosity and smoother fracture surfaces under optimized conditions. Overall, PLA consistently outperformed ABS across all settings, with an average tensile strength advantage of 47.5%. The results underscore the need for material-specific parameter tuning in FFF and offer practical insights for optimizing mechanical performance in applications demanding high structural integrity, including biomedical, aerospace, and functional prototyping.